Cognitive determinants of self-care behaviors among patients with heart failure: A path analysis - Nadrian, Haidar (Health Promot Perspect, 2018)
Background: Heart failure (HF) is a common clinical syndrome resulting from any structural or functional cardiac disorder that impairs the ability of ventricles to fill with or eject blood.Our aim in this study was to examine the possible direct/indirect effects of health belief model(HBM) constructs on self-care behaviors among HF patients. Methods: A secondary analysis was conducted on an HBM-based data set collected from 180 patients with HF who were recruited from a heart hospital in Tehran, Iran, during a prospective experimental study in 2008. A regression-based path analysis was conducted to examine the relationships between HBM constructs (as independent variables) and self-care behaviors (as dependent variable). Results: A conceptual path model was identified for the cognitive determinants of self-care behaviors among HF patients. Knowledge (β = 0.399), perceived barriers (β = 0.315) and susceptibility (β = 0.165) had direct effects on self-care (R2 = 0.512, P < 0.001). Perceived benefits, self-efficacy, severity and threat, locus of control and cues to action had indirect effects on self-care through the first three variables. Conclusion: HBM was found to be helpful in understanding direct and indirect associations between the cognitive determinants and self-care behaviors among HF patients. Based on this challenging path analysis, HF patients’ knowledge and perceived barriers and susceptibility are suggested as the most core categories while designing HF educational programs. Better understanding on such associations may lead nurses and health practitioners in designing properly informed stage-specific educational interventions aiming to foster self-care behaviors among HF patients.